Childlike images and education: Perspectives and possibilities on education of children - Leite, Cesar D.P. [UNESP]; Cammarota, Giovani (My University, 2020)
This chapter aims to discuss the formation of the teacher and the production of images by children. To do so, the text is organised in four blocks, each one focusing in a set of conceptual elements. The first one discusses two ways of conceiving the formation of the teacher: an instrumental way and a reflective way. It shows that both ways are in close affinity with a dogmatic image of thought and, therefore, they determine a dogmatic image of formation and childhood. The second block discusses cinema and the production of images by children, emphasizing that adults usually relate themselves with the childlike images from an interpretative point of view and from a modelled subjectivity. The third block invests in a line of escape: it discusses the potentia of childlike images. Those images create new spacialities and new temporalities deslocating the expectations of the adults, in particular of the teachers. The images create a becoming-child, a crumble in the dogmatic image of thought. Lastly, the fourth block broadens the ideas of the third one and discusses that the crumble in the dogmatic image of thought by the children’s images cause us to think a formation without an image or an immanent formation which does not previously know what it means to form, what it means to think, what it means to produce images, what it means to be a child and, therefore, invests in the event.
Keywords: Dogmatic image of thought; Formation of teachers; Production of images